2007
DOI: 10.1021/jp0710638
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of σ-Diatropicity of the Cyclopropane Molecule

Abstract: Spatial models of the current density field induced in the cyclopropane molecule by stationary, homogeneous magnetic fields, parallel to either the C3 or the C2 symmetry axis, have been constructed. A compact, abridged representation of the models is given via stagnation graphs that convey essential information. Maps of streamlines and moduli are also reported to complete current models that have proven useful to rationalize magnetic tensor properties, that is, magnetizability, 1H and 13C nuclear shieldings, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 51 publications
11
111
0
Order By: Relevance
“…Moreover, the main feature of the strong diatropic circulation in [c-C 3 H 6 ], which reaches maximal intensity (j max = 0.121 a.u.) outside the line of carbon centers [64,65], accounts well for the slight broadening of the NICS zz -scan curve (halfband width > 3 Å). The calculation of the CMO-NICS zz values for cyclopropane in D 3h symmetry showed that the Walsh orbitals HOMO,-1 (2e′), being σ-type MOs, have positive NICS zz value of 22.2 ppm, the HOMO-2,-3 (1e″), being π-type MOs, have also positive NICS zz value of 8.1 ppm and therefore induce σ-and π-type paratropic ring currents, respectively.…”
Section: The Case Of the [C-li 3 ] + And Cyclopropane 2e-σ-aromaticsmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, the main feature of the strong diatropic circulation in [c-C 3 H 6 ], which reaches maximal intensity (j max = 0.121 a.u.) outside the line of carbon centers [64,65], accounts well for the slight broadening of the NICS zz -scan curve (halfband width > 3 Å). The calculation of the CMO-NICS zz values for cyclopropane in D 3h symmetry showed that the Walsh orbitals HOMO,-1 (2e′), being σ-type MOs, have positive NICS zz value of 22.2 ppm, the HOMO-2,-3 (1e″), being π-type MOs, have also positive NICS zz value of 8.1 ppm and therefore induce σ-and π-type paratropic ring currents, respectively.…”
Section: The Case Of the [C-li 3 ] + And Cyclopropane 2e-σ-aromaticsmentioning
confidence: 72%
“…The CMO-NICS zz results are nicely mirrored on the shape of the NICS zz -scan curve of cyclopropane. It is interesting to notice that Pelloni et al [65] demonstrated that both the large negative NICS value and anisotropies of cyclopropane are mainly determined by the in-plane components rather than the more relevant out-of-plane contribution. The existence of σ-aromaticity in cyclopropane has recently been challenged by ab initio valence bond (VBSCF/cc-PVTZ) computations which revealed directly that the σ-aromatic stabilization energy of cyclopropane is, at most, 3.5 kcal/mol relative to propane [66].…”
Section: The Case Of the [C-li 3 ] + And Cyclopropane 2e-σ-aromaticsmentioning
confidence: 99%
“…The (13s10p5d2f/8s4p1d) uncontracted Gaussian basis set, used in previous near Hartree-Fock (HF) calculations [35,49,50], was employed. For consistency, molecular geometries of acetylene and ethylene were fully optimized at the HF level using the same basis set.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…The interested reader can find details of the computational procedure in these papers [32][33][34][35][36][37][38][39], which demonstrate that the classical formulae, Eqs. (1)-(4), provide practical computational recipes, as well as powerful interpretative tools, useful to rationalize the molecular magnetizability (1) and the shielding of a given nucleus (2) -or equivalently quantities (3) and (4) -via models of the induced current density J B invariant in a gauge translation [40].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation